If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(6 + -5x) + -2(3 + 6x) = 0 (6 * 9 + -5x * 9) + -2(3 + 6x) = 0 (54 + -45x) + -2(3 + 6x) = 0 54 + -45x + (3 * -2 + 6x * -2) = 0 54 + -45x + (-6 + -12x) = 0 Reorder the terms: 54 + -6 + -45x + -12x = 0 Combine like terms: 54 + -6 = 48 48 + -45x + -12x = 0 Combine like terms: -45x + -12x = -57x 48 + -57x = 0 Solving 48 + -57x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-48' to each side of the equation. 48 + -48 + -57x = 0 + -48 Combine like terms: 48 + -48 = 0 0 + -57x = 0 + -48 -57x = 0 + -48 Combine like terms: 0 + -48 = -48 -57x = -48 Divide each side by '-57'. x = 0.8421052632 Simplifying x = 0.8421052632
| 5(3x-2)=(2x-1) | | g(x)=3-9x | | 9(8+5m)= | | -8v+3(v+3)=14 | | 4(9x+8)-9(6-3x)= | | (x+4)(x+2)-3=0 | | (8x-4)+92=180 | | f(x)=x-17 | | 5(7x-8)-6(12x-4)= | | y=-9+5 | | 60+8x=80+6x | | 36x^2+16y^2+9z^2-144=0 | | 3z+5z-7z=7 | | 3/5x-7 | | 9(w+3)=3w+15 | | 6(3x-3)-(4+5x)= | | 2a-3=-5a+11 | | (fx)=2x-6 | | f(x)=x^2-10x+8 | | 25-64z^2=0 | | 20q-4q+q-15q=18 | | 420=16x*16x+27x | | 6(7x-3)-6(4-3x)= | | -3y+2+2y-5= | | 6n=30+3[n-4]forn | | 5(3x+6)+3(7x+6)= | | g(x)=27-3x | | 5z=1.7+3.8 | | lne^21/3 | | 22+e^3x=30 | | 20r-17r=15 | | -5(x+7)-43=3-56 |